Creating electronic screens in a hospital information system using nursing classifications - Dorothea Maria Beckers Marques de Almeida; Cassiana Mendes Bertoncello Fontes (Universidade Federal de Goias, 2013)
Electronic health records aim at providing greater readability and safety in documenting nursing actions. Using the nursing classifications of an information system organizes, standardizes and retrieves the data considered essential to plan individualized care and the results evaluation from the interventions. The objective was to describe the development of the Nursing Care Systematization stages using Nursing Classifications in a Hospital Information System. Cross-mapping was performed of the care plan content and the printed version, at a Semi-Intensive Care Unit. Excel spreadsheets were included according to the systematization stage and electronic screens permitted to record the nurses' clinical evaluation. The electronic documentation permitted faster data input and retrieval, in addition to stimulating diagnosis accuracy and evaluating the interventions by means of result indicators. Descriptors: Nursing Diagnosis; Nursing Process; Nursing Care; Nursing Informatics.